Identification and Pathogenicity of Fungal Pathogens Associated with Stem End Rots of Avocado Fruits in Kenya. (9th July 2020) - Wanjiku, E. K.; Waceke, J. W.; Wanjala, B. W.; Mbaka, J. N.
Abstract : Losses associated with stem end rot (SER) of avocado fruits have been reported in all avocado growing regions of the world. In Kenya, mature avocado fruits present SER symptoms during storage and marketing, but the disease causal agent(s) has not been established. This study aimed to identify the fungal pathogen(s) associated with avocado SER in Kenya and evaluate its pathogenicity. Fungal isolates were collected from symptomatic avocado fruits from randomly selected orchards and major markets within Murang'a County, a major avocado growing region in Kenya, between September 2017 and March 2018. A total of 207 and 125 fungal isolates, recovered from orchards and major markets, respectively, were identified morphologically and further confirmed by molecular techniques. The identified isolates were Lasiodiplodia theobromae (39.8%), Neofusicoccum parvum (24.4%), Nectria pseudotrichia (18.4%), Fusarium solani (7.2%), F. oxysporum (5.1%), F. equiseti (3.9%), and Geotricum candidum (1.2%). Geotricum candidum was exclusively recovered from fruits from the market. In the pathogenicity test, L. theobromae, N. parvum, and N. pseudotrichia caused the most severe SER symptoms. Consequently, they were considered to be the major pathogens of SER of avocado fruits in Kenya. To our knowledge, this is the first report of SER pathogen of avocado fruits in Kenya. Given the significant contribution of avocado fruits to household income and foreign exchange in Kenya, this information is significant to further develop management strategies of postharvest loss of avocado fruits in Kenya.